The Distributive Impact of Terms of Trade Shocks - Bussolo, Maurizio; Luongo, Patrizia (World Bank, Washington, DC, 2017)
The halving of oil prices, which happened in a short period between late 2014 and the first months of 2015, has generated major terms of trade losses for oil exporting countries. Even if the oil producing sector normally employs a small group of workers and oil export revenues tend to be concentrated in a few firms and in government accounts, these relative price changes have economy-wide effects and significant distributive impacts. This paper describes and quantifies the channels of transmission from the drop in oil prices, to changes in welfare distribution at the household level. Using a macro-micro simulation model, the paper assesses how this shock affects poverty, inequality, and shared prosperity for the case of the Russian Federation. The oil price reduction generates a reverse Dutch disease that impacts sectoral employment, factor returns, and consumption prices. It causes a contraction of employment and wages in more skill-intensive (non-tradable) sectors, and a reduction in consumption prices that is more pronounced for nonfood than for food goods. When these shifts are mapped to changes in incomes at the micro level, all households are affected. Poverty rates could increase by 1 to 4 percentage points, depending on the poverty line used. At the US$10 a day threshold, for example, 4.1 million additional people fall into poverty. Along the consumption distribution, richer people are affected more than those in the bottom 40 percent. However, this minor progressive impact may be reversed due to increases in unemployment and cuts in social programs (transfers).